Evaluation of the Growth Performance of Snails Fed Different Forages under Intensive Management - Odo, B.I.; Orji, A.C. (Pakistan Journal of Nutrition, 2010)
A six-week old experiment was conducted during the early rainy season of the year to investigate the growth performance of snails fed different forages under intensive rearing. The different forages used in the study constituted the treatment groups and they included: Fluted pumpkin (Telferia occidentalis) leaves (TA), African Spinach (Amaranthus sinensis) leaves (TB), Pawpaw (Carica papaya) leaves (TC) and formulated mash (TD). Thirty two (32) snails of 3 weeks old were divided into the four treatment groups of eight (8) snails each in a completely randomized design. Each treatment group was replicated twice. Result of data analysis showed that there was significant difference (p